An Unusual Cause of Dysuria in a 30-Year-Old Woman. Issue 2 (March 2016) - Nuckchady, Dooshanveer; Harris, Dana M.; Petrou, Steven P.; Brumble, Lisa M.
Abstract : Abstract: Although Mycobacterium tuberculosis typically causes respiratory infections, it is also associated with extrapulmonary disease. Urogenital tuberculosis accounts for 27% of extrapulmonary cases and most often occurs in immunocompromised persons. It can present as a localized genitourinary infection or may be part of a disseminated infection. Urogenital tuberculosis should be considered in the differential diagnosis of patients with persistent dysuria and pyuria. We present a case of genitourinary tuberculosis in an immunocompetent host. The diagnosis was initially missed, and the patient was treated with multiple ineffective courses of antibiotics. The case highlights the difficulties in diagnosing genitourinary infections due to Mycobacterium tuberculosis .